FINANCIAL FEASIBILITY OF CALIFORNIA PAPAYA FARMING IN SUKOHARJO DISTRICT, PRINGSEWU DISTRICT - Puspita, Putri Fina; Fitri, Annisa; Sutarni, Sutarni; Saty, Fadila Marga (Universitas Galuh, 2024)
The agricultural subsector that supports the economy in Indonesia is horticulture. There are various types of papaya fruit, including California papaya. The potential for papaya fruit is quite large for development. Papaya cultivation is apart from the problems that often arise, such as those that occur in Sukoharjo District, Pringsewu Regency. The problems faced include the high prices of fertilizers and pesticides used, the presence of pests that damage trees and fruit on plants which causes revenue to decrease, a profit that occurs. So it is necessary to carry out an analysis of the feasibility of California papaya farming from a financial aspect, a sensitivity analysis of California papaya farming in Sukoharjo District if there are changes in factors that can influence benefits and costs. The results obtained by California papaya farming based on financial aspects were declared feasible to be cultivated and developed with an NPV value of IDR 21,704,307, IRR 37%, Net B/C 1.96, a sensitivity analysis of California papaya farming was declared unfeasible if there was an increase in fertilizer costs of 18% with NPV –Rp 17,486,037.